Effects of two different cooling impact treatments on the thermal damage and mechanical properties of high-temperature granite - Xingchen Liu; Feng Huang; Aichen Zheng; Dong Yang (Case Studies in Thermal Engineering)
To study the mechanical properties and damage characteristics of cooled high-temperature rocks, uniaxial compression tests on granite cooled using two different media (water and concrete) after high-temperature treatment at 200–800 °C were conducted. The stage damage characteristics of the rock were analyzed in terms of mechanical deformation, acoustic emission, and temperature field. A rock brittleness evaluation method for the entire deformation process, considering the stress–strain relationship and energy storage–dissipation mechanism of rocks, is proposed. Experimental results showed that, as the heating temperature increased, the mass loss rate, volume expansion rate, and wave velocity attenuation rate of the rock increased, whereas the specific heat capacity decreased. Under a uniaxial compression load, the failure mode of the rock samples evolved from splitting to conical failure as the heating temperature increased. The mass of the exfoliated rock debris was nonlinear and positively correlated with the heating temperature. The energy storage limit Uel, energy storage efficiency η, pre-peak brittleness index Kpre, post-peak brittleness index Kpost, and whole-process brittleness index K‾a of the rock decreased as heating temperature increased. Under the same high-temperature treatment conditions, the higher the thermal conductivity of the cooling medium, the more significant the cooling impact damage.